Penguatan Kapasitas Masyarakat Desa Cibarani dalam Pemanfaatan Minyak Sereh Wangi (Cymbopogon nardus) sebagai Bahan Baku Produk Turunan Bernilai Ekonomi - Eka Candra Lina; Hasmiandy Hamid; Prima Fithri; Yumhi Yumhi; Yusup Junaedi; Egi Adha Juniawan (Warta Pengabdian Andalas, 2024)
The discovery of active compounds such as citronellol, citronellal, and geraniol in citronella grass (Cymbopogon nardus) opens new opportunities for using essential oils derived from this plant. These compounds are well-known for their aromatic properties and various benefits in the derivative product industry. Combining these three compounds presents immense potential for developing high-quality products such as soaps, aromatherapy, and pesticides. Community engagement activities were conducted in Cibarani Village, Lebak Regency, Banten. The fertile land in Cibarani Village is well-suited for cultivating citronella grass (C. nardus). The activities began with outreach and training sessions to educate the local community on the potential of C. nardus essential oil. This initiative aimed to equip the community with adequate knowledge and skills to process C. nardus oil into various derivative products. The derivative products introduced included botanical pesticides for controlling pests in cultivated plants. This information is particularly beneficial for the Mekar Rahayu Farmers Group, enhancing their knowledge and understanding of the potential of C. nardus essential oil as a botanical pesticide. It is hoped that the community will be able to produce botanical pesticides for personal use and sale to other farmers, thereby increasing their income. Simultaneously, the team also collected samples of citronella grass from Cibarani Village for distillation. The C. nardus oil obtained was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) to identify the dominant compounds. The essential oil produced from citronella grass in Cibarani Village, based on GC-MS results, revealed the main components as geraniol at 25.53% with a retention time of 13.212 minutes, citronellol at 15.71% with a retention time of 12.694 minutes, and citronellal at 17.19% with a retention time of 11.422 minutes.